Nanofibrous antibiotic‐eluting matrices: Biocompatibility studies in a rat model. Issue 2 (23rd April 2019) - Passos, Patrícia C.; Moro, Juliana; Barcelos, Raquel Cristine Silva; Da Rosa, Higor Z.; Vey, Luciana T.; Bürguer, Marilise Escobar; Maciel, Roberto M.; Danesi, Cristiane C.; Edwards, Paul C.; Bottino, Marco C.; Kantorski, Karla Z.
Abstract: This study evaluated the biocompatibility of degradable polydioxanone (PDS) electrospun drug delivery systems (hereafter referred as matrices) containing metronidazole (MET) or ciprofloxacin (CIP) after subcutaneous implantation in rats. Sixty adult male rats were randomized into six groups: SHAM (sham surgery); PDS (antibiotic‐free matrix); 1MET (one 25 wt% MET matrix); 1CIP (one 25 wt% CIP matrix); 2MET (two 25 wt% MET matrices); and 2CIP (two 25 wt% CIP matrices). At 3 and 30 days, animals were assessed for inflammatory cell response (ICR), collagen fibers degradation, and oxidative profile (reactive oxygen species [ROS]; lipid peroxidation [LP]; and protein carbonyl [PC]). At 3 days, percentages of no/discrete ICR were 100, 93.3, 86.7, 76.7, 50, and 66.6 for SHAM, PDS, 1MET, 1CIP, 2MET, and 2CIP, respectively. At 30 days, percentages of no/discrete ICR were 100% for SHAM, PDS, 1MET, and 1CIP and 93.3% for 2MET and 2CIP. Between 3 and 30 days, SHAM, 1CIP, and 2CIP produced collagen, while 1MET and 2MET were unchanged. At 30 days, the collagen fiber means percentages for SHAM, PDS, 1MET, 1CIP, 2MET, and 2CIP were 63.7, 60.7, 56.6, 62.6, 51.8, and 61.7, respectively. Antibiotic‐eluting matrices showed similar or better oxidative behavior when compared to PDS, except for CIP‐eluting matrices, which showed higher levels of PC compared to SHAM or PDS at 30 days. Collectively, our findings indicate that antibiotic‐eluting matrices may be an attractive biocompatible drug delivery system to fight periodontopathogens. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B, 2019.